ESTONIAN WEST COAST REVIVAL IN RETROSPECT: THE BIBLE AS A TOOL FOR INTERPRETING CHANGE - Toivo PILLII (Богословські роздуми: Східноєвропейський журнал богословʼя)
The West Coast Revival in  Estonia, in the 1870s and 1880s, emphasised  conversion, ethical lifestyle and a joyful, experiential discipleship. This was a new, congregational paradigm that emerged in this movement, in the westernmost areas of Tsarist Russia. The Revival was deeply rooted in a fresh reading of the Bible, even if its adherents used simple and literal interpretation. Both the Moravian tradition and Swedish neopietism encouraged individual and collective hermeneutics. The Revival, being inspired by both, however, made conclusions that reached further: these awakened farmers separated from the Lutheran church, began to conduct baptism and communion independently, and discussed biblical passages between themselves in order to find guidance in the midst of religious changes. As a result,